2011
DOI: 10.1097/jto.0b013e31820d9d11
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of JAK2 Signaling by TG101209 Enhances Radiotherapy in Lung Cancer Models

Abstract: Introduction Persistent STAT3 activation contributes to lung carcinogenesis. Survivin, one of STAT3-regulated genes, is antiapoptotic and confers cancer radioresistance. Methods We tested whether TG101209, a small-molecule inhibitor of JAK2 (a STAT3-activating tyrosine kinase), affected survivin expression and sensitized lung cancer to radiation. We investigated whether inhibition of JAK2 signaling with TG101209 can be used to reduce survivin expression and enhance radiosensitivity of lung cancer cells in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 37 publications
4
34
0
Order By: Relevance
“…It has been demonstrated that the induction of c-jun expression in irradiated cells requires the activation of JAK3, but is impervious to the activation status of JAK1 and JAK2 (21). A recent study using TG101209, a small-molecule inhibitor of JAK2, found that JAK2 inhibition could be a promising strategy for lung cancer treatment (22). Therefore, it is important to define the role of the JAK2 pathway in irradiated solid tumors, because better therapies are desperately needed to treat these malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the induction of c-jun expression in irradiated cells requires the activation of JAK3, but is impervious to the activation status of JAK1 and JAK2 (21). A recent study using TG101209, a small-molecule inhibitor of JAK2, found that JAK2 inhibition could be a promising strategy for lung cancer treatment (22). Therefore, it is important to define the role of the JAK2 pathway in irradiated solid tumors, because better therapies are desperately needed to treat these malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that phosphorylation of ERK could contribute to the low levels of apoptosis induced by radiotherapy in mutated KRAS lung cancer cells. This work suggests that KRAS mutation status is one potential factor associated with increased resistance to radiation-induced apoptosis in lung cancer cells [70]. The same group has recently shown that the specific inhibition of JAK2 by the novel molecule TG101209, induces radiosensibility through inhibition of phosphorylation of STAT3 and reduced expression of survivin in HCC2429 lung cancer cells.…”
Section: Role Of Egfr Pathways In Resistance and Sensibility To Radiomentioning
confidence: 97%
“…The same group has recently shown that the specific inhibition of JAK2 by the novel molecule TG101209, induces radiosensibility through inhibition of phosphorylation of STAT3 and reduced expression of survivin in HCC2429 lung cancer cells. Moreover, the inhibition of survivin by treatment with TG101209 in experiments in vivo, was related to increased apoptosis, reducing tumor proliferation and vascular density [70]. Lu et al demonstrated that overexpression of survivin leads to radioresistance in H460 lung cancer cells by inhibiting apoptosis and promoting cell survival, however, when survivin is inhibited by antisense oligonucleotides the cytotoxic effect of radiation is enhanced [71].…”
Section: Role Of Egfr Pathways In Resistance and Sensibility To Radiomentioning
confidence: 99%
“…The most commonly used method to determine Janus kinase activity are radioisotope methods [4], phosphor specific antibodies [5], surface plasmon resonance [6] and fluorescence resonance energy transfer-based systems [7].…”
Section: Introductionmentioning
confidence: 99%